2012
DOI: 10.1260/0144-5987.30.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Petrological and Geochemical Investigations of Rajpardi Lignite Deposit, Gujarat, India

Abstract: The present paper entails the petrographic and chemical characteristics of the lignite samples drawn from the Rajpardi lignite deposit of Bharuch district, Gujarat. This lignite contains a high concentration of huminite which is dominated by telohuminite, followed by detrohuminite. Liptinite and inertinite macerals are very low in concentration. The dominant microlithotype is humite. Its elevated volatile matter and high hydrogen content depicts its perhydrous nature. The study reveals that this lignite origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…This is also evident from a low to moderate but positive correlation between TPI and clastic minerals (r = 0.42 in Tadkeshwar, r = 0.17 in Vastan, and r = 0.10 in Rajpardi seams). A similar observation was also noticed in Nagaland coals of north-eastern India (Singh et al 2012b). However, a low but negative correlation value exists between GI and TPI values (r = -0.09 for Tadkeshwar lignite, and r = -0.02 for Vastan lignite of Cambay Basin).…”
Section: Paleomiressupporting
confidence: 79%
“…This is also evident from a low to moderate but positive correlation between TPI and clastic minerals (r = 0.42 in Tadkeshwar, r = 0.17 in Vastan, and r = 0.10 in Rajpardi seams). A similar observation was also noticed in Nagaland coals of north-eastern India (Singh et al 2012b). However, a low but negative correlation value exists between GI and TPI values (r = -0.09 for Tadkeshwar lignite, and r = -0.02 for Vastan lignite of Cambay Basin).…”
Section: Paleomiressupporting
confidence: 79%
“…In Tadkeshwar upper and lower seams the ash content is 6.4% and 12% respectively ( (Table 2). Though the sulfur content is moderate but few sections have high sulfur content which is attributed to marine influence as reported by Singh et al (2010Singh et al ( , 2012. They have further reported that the formation of Vastan and Rajpardi lignites took place in limnic to limno-telmatic environment under a medium to very high water cover which resulted into anaerobic preservation of organic matter with increasing bacterial activity.…”
Section: Chemical Attributesmentioning
confidence: 73%
“…Facies models mainly based on petrographic elements have been used to discuss the evolutionary history of the paleomires of Kachchh Basin. A number of researchers (Cohen and Spackman 1972;Styan and Bustin 1983;Cohen et al 1987;Calder et al 1991;Grady et al 1993;Hawke et al 1996;Singh and Singh 1996;Shearer and Clarkson 1998;Jasper et al 2010;Singh et al 2010a, b;Suárez-Ruiz et al 2012;Singh et al 2012aSingh et al , b, 2014 have attempted paleoecological reconstructions using petrological tools. Recently, O'Keefe et al (2013) have made a detailed discussion on 'coal rank' and 'coal type' and relation of latter to the environment of peat formation, the climate of peat formation, and the decompositional history of the mire.…”
Section: Depositional Environmentmentioning
confidence: 99%
“…It is evident from the figure that in Panandhro area maximum gelification occurred during the formation of Seam-II while in Matanomadh area high gelification was observed during the formation of Seams I, II, and V. Further, in Panandhro area, GWI was high during the formation of seams I, II, and V while in Matanomadh area the GWI was high during the formation of seams I and VI. Singh et al (2012a) proposed a ternary model for understanding the paleomires of the Eocene lignite deposit of Rajpardi. This is based on maceral composition as well as clastic minerals.…”
Section: Depositional Environmentmentioning
confidence: 99%